Comparative response on the accumulation of inorganic phosphate in leaf of Basella alba to low and high temperature - Haque, Md Shahidul; Islam, Md Monirul; Yeasmin, Tanzima (Journal of Bio-Science, 2014)
Context: Basella alba is a green vegetable and grows in both winter and summer; however the temperature sensitivity on metabolic regulation in this species is not clarified. Objective: To find the role of low and high temperature induced regulation of metabolic functions particularly alteration and accumulation of inorganic phosphate in leaf. Materials and Methods: Plants grown in pot were exposed to cold (8°C) for 24h, 48h and 72h periods and the respective controls were kept in ambient room temperature for the above mentioned time. For high temperature induced plants, they were exposed to 45°C with full aeration along with sufficient water. Control pot was used similarly in room temperature; however, the temperature was maintained 30°C by using air cooling system (AC). Results: Low temperature causes the higher inorganic phosphate level in leaf and was increased by 33.6%, 34.7% and 62.8% respectively when compared to the respective controls. Therefore, it is assumed that short term exposure has mild effect on phosphate accumulation in leaf; conversely as the time extended, the synthesis assumed to be higher and increased time dependently. Similarly, the inorganic phosphate concentrations were increased by 27.8%, 37.5% and 74.9% respectively whenever the plants were exposed to high temperature (45°C). Taken together, a faster increase in accumulation of phosphate in leaf was mediated by high temperature for prolonged exposure. Conclusion: The plants exposed to both abiotic stresses cause the release of inorganic phosphate which may participate in the survival of the species in the adverse environment DOI: http://dx.doi.org/10.3329/jbs.v20i0.17719 J. bio-sci. 20: 83-90, 2012